Penerapan Asas Primum Remedium Tindak Pidana Lingkungan Hidup - Kania Tamara Pratiwi; Siti Kotijah; Rini Apriyani (Faculty of Law, Universitas Pattimura, 2021)
The principle of primum remedium emphasizes the application of Article 84 of Law Number 32 of 2009 concerning Protection and Management of the Environment, whose actions do not need to be proven, it is clear that committing environmental crimes, which in environmental law enforcement is rarely applied by judges in the Supreme Court decisions. Doctrinal research with the adjudication of judges' decisions. The application of the primum remedium principle in environmental law enforcement in B3 waste cases does not need to be proven and clearly commits pollution and destruction of the environmental environment, thus providing a deterrent effect for perpetrators and anyone who will commit environmental crimes. The formulation of the classification of criminal elements is clearly and firmly regulated in the UUPPLH criminal provisions relating to the application of the two principles of primum remedium and ultimum remedium. The validity of criminal law as primum remedium with Decision Number 487 / Pid.B / LH / 209 / PN Sm, does not pay attention to formal offenses so that environmental crimes can be released from criminal threats. For this reason, the judge's understanding and certification in deciding cases related to environmental law must be evaluated and monitored for the judge.